Narcissistic and dependent traits and behavior in four archetypal 2-person, 2-choice games - Reed, Lawrence Ian; Cooke, Lily; Kasaba, Isabella; Harrison, Eleanor; Hooley, Jill M. (Frontiers in Psychiatry, 2024)
Introduction The characteristic behaviors we use to define personality pathology arise from specific interpersonal interactions. In an effort to create a laboratory-based context in which behavior might be expected to be influenced by particular personality traits, we used four 2-person, 2-choice games (the Prisoner’s Dilemma, Chicken, Leader, and Hero games) to create a simulated interaction and focused specifically on narcissism and dependency. Method An online sample of 1137 (35% male, M age = 38.46 years, SD age = 13.20) participants completed brief, self-reported measures of trait narcissism and dependency and played one of the four games. Before deciding how to act or react, participants received either no message, a promise to cooperate, or a threat to defect from a (confederate) partner. Results When receiving no message, those who cooperated in the Prisoner’s Dilemma had lower trait narcissism, while those who defected in the Chicken and Leader games had higher trait narcissism. Also with no message, participants who cooperated in the Hero game had higher trait dependency. Promises only affected the relationship between trait narcissism in the Leader game while threats only affected the relationship between trait dependency in the Chicken game. Discussion These findings add to the limited behavioral research on personality pathology and largely support established interpersonal conceptualizations and models. Future work might extend these findings using even more ecologically valid approaches to explore the behavioral correlates of personality traits that have important implications for interpersonal interactions.